2010
DOI: 10.1111/j.1467-6486.2009.00870.x
|View full text |Cite
|
Sign up to set email alerts
|

Governing Knowledge Sharing in Organizations: Levels of Analysis, Governance Mechanisms, and Research Directions

Abstract: We discuss and examine recent claims that research on knowledge processes has paid insufficient attention to micro (individual) level constructs and mechanisms and to the role of formal organization in governing knowledge processes. We review knowledge sharing research published in 13 (top academic plus top practitioner-oriented) journals in the period 1996-2006 in relation to these two propositions. The review confirms the claim that the knowledge sharing literature is preoccupied with constructs, processes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
561
1
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 533 publications
(623 citation statements)
references
References 178 publications
(223 reference statements)
13
561
1
12
Order By: Relevance
“…We did not specifically analyze whether the knowledge components represented location or non-location bound knowledge (Rugman & Verbeke, 2001), or the translation work required to utilize knowledge from other locations, nor did we analyze in detail what knowledge was explored but not mobilized; further research could investigate these aspects. Given that applying a middle management perspective to questions of MNC knowledge flows yielded theoretical insights in this study, further studies could develop this research avenue: more fine-grained understanding of subsidiary managers" knowledge exchanges is needed to explore fully how their actions (or inactions) lead to creative and innovative (Kanter, 1982) and strategic outcomes (Floyd & Wooldridge, 1994, and the influence of the MNC"s knowledge governance mechanisms in directing their actions (Foss, 2007;Foss et al, 2010).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not specifically analyze whether the knowledge components represented location or non-location bound knowledge (Rugman & Verbeke, 2001), or the translation work required to utilize knowledge from other locations, nor did we analyze in detail what knowledge was explored but not mobilized; further research could investigate these aspects. Given that applying a middle management perspective to questions of MNC knowledge flows yielded theoretical insights in this study, further studies could develop this research avenue: more fine-grained understanding of subsidiary managers" knowledge exchanges is needed to explore fully how their actions (or inactions) lead to creative and innovative (Kanter, 1982) and strategic outcomes (Floyd & Wooldridge, 1994, and the influence of the MNC"s knowledge governance mechanisms in directing their actions (Foss, 2007;Foss et al, 2010).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Departing from the common emphasis on using the subsidiary as level of observation of knowledge flows and responding to the need for micro-level investigations (Foss, Husted, & Michailova, 2010;Foss & Pedersen, 2004;Minbaeva, Foss, & Snell, 2009), we pursued an individual-level approach that seeks to unravel explanatory mechanisms of organizational knowledge flows at the level of individuals by focusing at their actions and interactions (Felin & Foss, 2005;Felin & Hesterly, 2007). Fundamentally, knowledge flows depend on human interactions and people"s abilities to transfer knowledge Argote, Ingram, Levine, & Moreland, 2000;Argote, McEvily, & Reagans, 2003;Noorderhaven & Harzing, 2009): it is not units as such that exchange knowledge, but individuals within those units.…”
Section: Mnc Knowledge Flows At the Individual-level: The Central Rolmentioning
confidence: 99%
“…There is a gap in research at the "micro-level" of IJV manager action and interaction (Foss et al, 2010), concerning the "microfoundations" of learning within IJVs. This study asks what are the capabilities, actions and decisions that help IJV managers to learn from their partners, to develop capability from that learning, and to build the absorptive capacity needed to do so.…”
Section: Introductionmentioning
confidence: 99%
“…IJVs offer a channel for learning opportunities (Park & Ghauri, 2011) and provide a means of developing ventures that obtain knowledge, skills and competencies from partners with complementary capabilities (Beamish & Berdrow, 2003;Inkpen, 2008;Kwon, 2008;Tsang, 2002). IJVs need to ensure appropriate learning processes because their capability to learn and diffuse accumulated knowledge stocks, flows and processes from their IJV partner firms is critical for their development (Beamish & Berdrow, 2003;Park & Ghauri, 2011); learning is their source of competitive advantage (Foss, Husted & Michailova, 2010;Glaister, Husan, & Buckley, 2003;Kandemir & Hult, 2005). The difficulty of managing IJVs, where they face considerable barriers to knowledge transfer and learning in comparison with single firms (Pak et al, 2009), however, has been found to lead to a high failure rate (Beamish & Delio, 1997;Pak, Ra, & Park, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [4] state that knowledge transfer is designed to transform individual knowledge into organizational knowledge. Knowledge transfer is considered as a significant component of knowledge management success [5].…”
Section: Introductionmentioning
confidence: 99%